Tough but not rough: what does biomechanics feed into the rugby scrum? - Preatoni, E.; Cazzola, D.; Stokes, K. A.; England, M. E.; Trewartha, G. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The aim of this paper is to present the "Biomechanics of the Rugby Scrum" project, a three-year research programme that thoroughly studied the kinematics and kinetics of rugby union scrummaging with a view to identifying safer scrum engagement techniques. The outcomes of the study will be analysed and their implications for injury prevention and performance will be discussed.